The Urgency of Islamic Guidance and Counseling for School Dropouts in Duampanua Subdistrict, Pinrang Regency. - Aisyah, Sitti; Astarina, Nella (Jurnal Mercusuar, 2020)
This research discusses the urgency of Islamic guidance and counseling for school dropouts in Duampanua District, Pinrang Regency, with the formulation of problems: 1. What factors cause school dropouts in Duampanua District, Pinrang Regency? 2. How is the effort of Islamic guidance and counseling for school dropouts in Duampanua District, Pinrang Regency? The objectives of this study are: 1. To find out the causes of school dropouts in Duampanua District, Pinrang Regency. 2. To determine the role of Islamic guidance and counseling for school dropouts in Duampanua District, Pinrang Regency. This research uses qualitative research. The research approach used is a Psychological approach and Guidance approach. The data sources in the study include several components ranging from the parents of the child, community leaders and the school dropouts themselves. The data collection techniques used in this study are observation, interviews, and documentation techniques. Data processing and analysis techniques use data reduction, data presentation, and conclusion drawing. The results showed that: a. The factors causing school dropouts in Duampanua District, Pinrang Regency are internal factors such as laziness and embarrassment. Meanwhile, external factors are factors that come from outside of a person, such as social environment problems, economic problems, family environment problems, and being scolded by parents. External factors have an influence such as social environment, family environment, economic problems, and unfulfilled child’s needs. b. The efforts of Islamic guidance and counseling for school dropouts in Duampanua District, Pinrang Regency include: 1. Being able to cultivate motivation and increase religiosity and improve the character of school dropouts. 2. The role of the counselor as a good guide helps to develop religiosity of school dropouts. The implication of this study is to become an understanding of the government and all stakeholders who have concern for the lives of school dropouts in Indonesia, especially Pinrang Regency government, and to become a reference for formulating a thought of Islamic guidance and counseling development in Indonesia and the role of parents in helping Islamic religious counselor.